Los Girasoles Ciegos: discutindo, através do filme e da obra homônima, a guerra civil espanhola com alunos avançados de espanhol/LE - Câmara, Yls Rabelo (2018)
The civil war was one of the most regrettable chapters in the recent history of Spain. More than eighty years have passed since its inception and the memories of war and postwar are still painful in the discourse of those who have suffered directly or indirectly as an event not to be forgotten by the trauma and lesson left behind. In this work we propose to analyze one of the most recent Spanish films and awarded, whose plot is developed in Ourense in the 1940s: Los girasoles ciegos, based on two of the four short stories of the book of the same name by Alberto Méndez. Based on the discussion of the content of this work, we aim to discuss the theme of the Civil War in the classroom, for students with advanced Spanish level and who have sufficient literacy to interact with content. Thus, we first present an overview of the circumstances that involved civil war in the guise of introduction; then we analyze the consequences of this war in the cinema and, more specifically, in the film Los girasoles ciegos. We base our considerations on area theorists such as Ramblado-Minero (2007), Ramos (2011) and Serber (2011). We conclude that subjects such as the Spanish Civil War, which raises debate in the classroom with advanced students of Spanish E/LE, should be explored in the form of a novel or film or both and brought to the context of the class in order to enrich classes and to promote, among the pupils, greater oral production and greater immersion in the language and cultures linked to it.